Hukum Kepemilikan Sisa Kain Jahitan - Fikri Al Munawwar Sirait; Dhiauddin Tanjung (TAFAQQUH, 2022)
This study aims to examine the concept of ownership from the perspective of Fiqh Muamalah, particularly in the context of human social relationships and daily life practices, such as the making of clothing by tailors. The method used in this research is an in-depth literature review, referring to various sources of Islamic law and the opinions of fuqaha (Islamic jurists) regarding ownership and its division. The results of the study indicate that ownership in Islam includes the rights to an object and its benefits, and can be divided into complete and incomplete ownership. Additionally, this research reveals the importance of tailors returning leftover fabric to the customer as a form of respect for ownership rights. The contribution of this study is to provide a clearer understanding of the importance of managing ownership in societal life, as well as to offer practical guidance for tailors in fulfilling their obligations to customers in accordance with the principles of Fiqh Muamalah